Hubungan Stres Psikologis dan Kualitas Tidur Siswa Kelas XII Kota Jambi Menjelang Seleksi PTN - Nabila Aisyah Syahla; Siti Nurhanifah; Aufi Adilla; Beny Rahim; Jelpa Periantalo; Muhammad Ilham; Dinda Agraiza (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to determine the relationship between psychological stress and sleep quality among 12th-grade students in Jambi City in the lead-up to the state university admissions process. The study employed a quantitative approach with a cross-sectional design involving 38 students selected using purposive sampling. Data collection was conducted using the Indonesian version of the DASS-Y questionnaire developed by Muskar and Rosyad, with a reliability of 0.930 and item-total correlation validity ranging from 0.328 to 0.753, while the Indonesian version of the PSQI, developed by Fauzi et al., used Cronbach’s Alpha with a reliability of 0.803 and content validity (CVI) ranging from 0.92 to 1.00. Data were analyzed using Pearson’s correlation test after meeting the normality assumption based on the Shapiro-Wilk test. The results showed that most respondents had normal levels of psychological stress (65.79%), yet the majority experienced poor sleep quality (86.84%). The analysis showed a significant relationship between psychological stress and sleep quality (p = 0.007; r = 0.431). It was concluded that the higher the level of psychological stress, the poorer the sleep quality experienced by students.